Analysis Of Students’ Critical Thinking and Independence of Learning Through Problem-Based Learning - Erinda Titik Rizki Fani; Baiduri Baiduri; Alfiani Athma Putri Rosyadi (Department of Mathematics Education University of Muhammadiyah Malang, 2018)
The purpose of this research was to describe the VIIIF students’critical thinking and independence of learning through problem-basedlearning. The type of this research was qualitative descriptive supportedquantitative data with 30 VIII F students as the subject.This study wasconducted for four times meetings. The data were taken by using observationsheet of their critical thinking and questionnaire of their independence oflearning. The result of data obtained in form of observations andquestionnaires which then descriptive analysis.The result showed that theircritical thinking on the aspect of giving explanation, concluding, set thestrategy and tactics of the categories as good and very good, while theirindependence of learning on the aspect of self-confidence, initiative, andresponsibility were independent.